The aesthetics of forming acting performance in children's theater performances - Hayder Jaafar Aldaghlawy (الاكاديمي, 2024)
The theatrical performance embodies a multi-faceted aesthetic taste that has emerged from the creative human consciousness. As human thinking evolved and developed a love for play and entertainment, it began to fill its aspects with singing, acting, shaping, and decorating. The basics of this study consist of the primary form of theatrical performance and its symbols, meanings, and the use of children's theater in efforts to achieve visual and kinetic events through harmony and development of various means until it became the fundamental and essential role in using the actor's tools as a tangible sign and nucleus in the formation of the theatrical performance. This medium is especially true when the theatrical act gains a diverse aesthetic formation to entertain and delight children.